FUNGATING SCROTAL MASS WITH FACIAL NERVE PALSY IN AN ADVANCED TESTICULAR EMBRYONAL GERM CELL TUMOUR : UNUSUAL OCCURRENCE - Abubakar Abdulkadir; Muhammad Sani Ibrahim (Ntec Specialist, 2016)
Background: Fungating scrotal mass and lower motor neuron facial nerve palsy (LMN-FNP) are unusual traits of testicular cancer. A 49-year-old farmer with recurrent right hemi-scrotal swelling that expeditiously grew to involve the whole scrotum. He had a nick on the swelling and the resultant ulcer extended rapidly over the mass and right groin. There were associated penile deformity and right lower leg swelling. The angle of his mouth became inclined to the left side with inability to close the right eye. He had right orchidectomy five years earlier for right testicular mass through the scrotal approach but no histology was done. On examination, he had a huge fungating scrotal mass that extends to the right groin with saxophone penile deformity. There were multiple left inguinal lymphadenopathies with right pedal oedema. There was grade III right LMN-FNP, tympanometry showed an absent acoustic reflex and pure tone audiometry revealed right sensorineural hearing loss. Computerized tomography (CT) scan of the abdominopelvic and temporomastoid regions showed metastatic deposits in the retroperitoneal group of lymph nodes and fallopian canal respectively. The patient was optimized and commenced on cytotoxic chemotherapy but five days after completing the first course he developed sudden inability to swallow, lapsed into unconsciousness and ceased breathing despite resuscitation effort. Conclusion: Fungating scrotal mass and facial nerve palsy from an advanced testicular germ cell tumour are unusual. Therefore, a high index of suspicion is essential for the diagnosis of testicular tumour secondaries as the cause of facial nerves palsy and the tumour invasion the cause of the fungating mass. It has a negative impact on patient's body image plus the quality of life and probably presaged poor outcome